2017
DOI: 10.5507/bp.2017.022
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells and serum levels of MMP-2, MMP-9 and VEGF as markers of the metastatic process in patients with high risk of metastatic progression

Abstract: Background and Aims. Metastases are a severe complication in cancer patients and biomarkers predicting their progression are still lacking for specific groups of patients. HER2 positive breast cancer (HER2 BC) patients on trastuzumab therapy are at risk of the development of unpredictable and often fatal central nervous system (CNS) metastases and castration resistant prostate cancer (CRPC) patients urgently need a marker of disease progression during therapy. Proposed metastatic markers: circulating tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
1
12
1
1
Order By: Relevance
“…In our study, the patients with PCa demonstrated a significantly higher concentration of serum VEGF (179.3 versus 123.3 pg/mL, resp.). The results obtained by Skerenova et al had shown higher levels to have occurred in men with castration resistant prostate cancer (CRPC) than in healthy men (332 versus 239 pg/mL); however, the median concentration in PCa group was much higher than in our results (332 versus 179.3 pg/mL) [ 67 ]. It may result from the assortment of patients, as Skerenova et al examined patients with highly advanced cancer.…”
Section: Discussioncontrasting
confidence: 83%
“…In our study, the patients with PCa demonstrated a significantly higher concentration of serum VEGF (179.3 versus 123.3 pg/mL, resp.). The results obtained by Skerenova et al had shown higher levels to have occurred in men with castration resistant prostate cancer (CRPC) than in healthy men (332 versus 239 pg/mL); however, the median concentration in PCa group was much higher than in our results (332 versus 179.3 pg/mL) [ 67 ]. It may result from the assortment of patients, as Skerenova et al examined patients with highly advanced cancer.…”
Section: Discussioncontrasting
confidence: 83%
“…Multivariate analysis indicated that serum MMP‐9 and HER2 ECD levels could accurately discriminate patients with brain metastasis from controls (Darlix et al, ). MMP‐2 serum levels have also been reported to be significantly higher in HER2‐positive breast cancer patients who developed central nervous system metastasis (Skerenova et al, ). High baseline serum MMP‐2 levels correlated with better DFS and OS in breast cancer patients treated with bevacizumab‐based neoadjuvant chemotherapy (BEVERLY‐2 study), while low baseline MMP‐9 associated with better OS and DFS (Tabouret et al, ).…”
Section: Diagnosis and Prognosis Of Cancers By Mmpsmentioning
confidence: 99%
“…In the past decade, many potential biomarkers have been discovered including circulating proteins, 36 mutated DNAs, RNAs, 37 , 38 and serum proteins. Serum markers are the simplest to measure for routine clinical assessments and epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%